The β5 subunit is essential for intact 26S proteasome assembly to specifically promote plant autotrophic growth under salt stress. Issue 3 (22nd October 2018) - Han, Jia‐Jia; Yang, Xiaoyuan; Wang, Qian; Tang, Lu; Yu, Feifei; Huang, Xiahe; Wang, Yingchun; Liu, Jian‐Xiang; Xie, Qi
Summary: The ubiquitin 26S proteasome (26SP) system efficiently degrades many key regulators of plant development. 26SP consists of two subcomplexes: the catalytic 20S core particle (CP) and the 19S regulatory particle (RP). Previous studies have focused on 19S RP; whether there is a specific subunit in 20S CP that has a stress‐related biological function in plants is unclear. PBE1, one of the β5 subunits of Arabidopsis proteasome CP, is essential for the assembly and proteolytic activity of 26SP in salt‐stressed seedlings. The expression of PBE1 is stress‐induced. During the transition from seed germination to autotrophic growth in salt‐stressed seedlings, loss of PBE1 function results specifically in arrest in developmental transition but not in germination and post‐germination growth. PBE1 is also important for other types of proteasome stress and Endoplasmic Reticulum (ER) stress. PBE1 modulates the protein level of the transcription factor ABI5 and thereby down‐regulates the expression of several genes downstream of this key regulator which are known to be essential for plant growth under stress. Collectively, our results showed PBE1‐mediated intact proteasome assembly that is essential for successful autotrophic growth, and revealed how PBE1 mediated stress proteasome functions to control both proteasome activity and abscisic acid (ABA)‐mediated stress signaling in plants.